Seabed scour by currents near platforms - Carstens, T. (author) (University of Alaska, 1976)
The gravity platforms in the North Sea, sitting directly on granular seabeds, may be undercut by scour and need scour protection. Conventional methods of protections are developed for structures 1or 2 orders of magnitude smaller and seem unnecessarily conservative when scaled to these larger sizes. The reason is that some of the flow details that exert extra stresses on the bed, are not preserved during scale-up. Some new ideas for scour protection are discussed. These are all built into the structure so as to reduce expensive offshore operations as much as possible. A breakthrough in protection technique is anticipated before long as a result of the present effort in several countries to come up with satisfactory designs.